INNOVATIVE TEACHING METHODS IN HIGHER EDUCATION INSTITUTIONS DURING A FULL-SCALE INVASION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The article provides a theoretical analysis of the problem of innovative teaching methods in higher education institutions during a full-scale invasion, which contributed to clarifying the content of the basic concepts of research: "innovation", "innovative teaching methods", and "full-scale invasion". It is proved that the introduction of innovative teaching methods in higher education institutions in the context of full-scale invasion will contribute to improving the quality of education by providing students with more opportunities for self-development, critical thinking, and a creative approach to problem solving; as well as active involvement of students in the learning process, creating a supportive and creative educational environment in the HEI. The purpose of the article is to analyse the challenges faced by higher education institutions in the context of full-scale invasion and to identify innovative teaching methods in HEIs during a full-scale invasion. The main objectives are: to analyse leading scientific works on the research problem and to substantiate the theoretical foundations for understanding the concepts of "innovation", "innovative teaching methods", and "full-scale invasion"; to identify the challenges faced by higher education institutions in this context; and to determine innovative teaching methods appropriate for such conditions.Methods. The achievement of the stated aim and the solution of the research objectives were carried out with the help of general scientific and specific scientific methods appropriate to the purpose and tasks of the study. The use of a systematic approach made it possible to view the teaching process in higher education institutions as a system with structural components, which define the content and implementation of innovative methods. This methodology enabled the identification of the significance of innovative teaching methods in HEIs during the full-scale invasion.Results. The study clarified the key concepts of "innovation", "innovative teaching methods", and "Russian-Ukrainian war", and identified the challenges faced by higher education institutions in the context of full-scale invasion, such as changes in teaching format; rapid adoption of digital tools by educators; shifts in the labor market affecting specialist competencies; teacher migration abroad; and the psychological condition of all educational participants. The research also identified a variety of innovative teaching methods applicable in this context, including simulation games, project-based learning, group work using digital platforms like Padlet and Miro, case studies, problem-based learning, the flipped classroom, guest lectures, practitioner involvement, and gamification.Conclusions. The study confirms that the full-scale invasion has created specific challenges for universities seeking to maintain quality education and student support in difficult conditions. It is substantiated that innovative teaching methods offer valuable solutions for maintaining effective learning and engagement. The challenges influencing the integration of these methods are outlined, and the potential for implementing innovative strategies in higher education institutions under martial law is emphasized.
Keywords: full-scale invasion; higher education institution; innovative teaching methods; university students